A rare presentation of invasive mole with an arterio-venous malformation: a case report - Dhillon, Atmajit Singh; Pathak, Vartika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Gestational trophoblastic disease comprises of various pathologies with hydatid form mole bring a common etiology. Emergency admissions of patients of gestational trophoblastic disease is very rare. Here we present a case report of an emergency admission of patient with hydatidiform mole and severe bleeding and then was managed for the same during the course of hospital stay.